2018
DOI: 10.1183/13993003.02070-2017
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal antibiotic exposure and childhood asthma: a population-based study

Abstract: Antibiotic use during infancy alters gut microbiota and immune development and is associated with an increased risk of childhood asthma. The impact of prenatal antibiotic exposure is unclear. We sought to characterise the association between prenatal antibiotic exposure and childhood asthma.We performed a population-based cohort study using prescription records, hospitalisation records and physician billing claims from 213 661 mother-child dyads born in Manitoba, Canada between 1996 and 2012. Associations were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
92
1
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(104 citation statements)
references
References 43 publications
(63 reference statements)
7
92
1
4
Order By: Relevance
“…There are alternative explanations for the findings of LOEWEN et al [25]. Antibiotics substantially alter the composition of microbiota and their metabolite production.…”
mentioning
confidence: 53%
See 3 more Smart Citations
“…There are alternative explanations for the findings of LOEWEN et al [25]. Antibiotics substantially alter the composition of microbiota and their metabolite production.…”
mentioning
confidence: 53%
“…LOEWEN et al [25] interpreted their finding, that maternal antibiotic use in the periods before, during and after pregnancy was associated with childhood asthma, as evidence that antibiotics taken in pregnancy, specifically, may not be causally associated with childhood asthma. They offered alternative hypotheses for their findings.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…However, in a Swedish study by Örtqvist et al [59] antibiotic exposure in fetal life was associated with increased risk for asthma in a cohort analyses but not sibling analyses, suggesting that the link between antibiotic use and atopy may be confounded by shared familial risk factors. Furthermore, a recent study showed that maternal antibiotic exposure during pregnancy is associated with a dose-dependent increase in child asthma risk [60], but so was maternal antibiotic use before pregnancy and in the 9 months postpartum. However, in a well-designed sibling-control study, Mulder et al [61] found prenatal antibiotic use to be predictive of childhood asthma even compared to sibling controls.…”
Section: Maternal Microbiota During Pregnancy and Offspring Immune-rementioning
confidence: 99%